Economic effects of dried pear production using combined technology - Vukoje, Veljko; Pavkov, Ivan; Babić, Mirko (Economics of Agriculture, 2010)
This paper analyses the expenses and results of dried pear production using combined technology. The research refers to a dryer of the capacity 450 kg of raw material per day, which is suitable for production on family farms. Drying of pears lasts for 20 days, while the period for drying all fruit lasts 135 days per year in total. Cost price of dried pear, in packages of 100-500g, is 376. 8 RSD/kg (3. 59 €/kg). In the cost price structure the expenses of dried pear (56. 7%) are the highest, while energy costs are low (2. 8%). Substitution of wheat straw by natural gas in the process of convective drying increases energy costs to the still acceptable amount of 6. 9%, so it can be an alternative in the present production conditions. The wholesale price of 590 RSD/kg (5.62 €/kg) makes the proft of 3,376 €/20 days in dried pear production.